Age and Menopausal Status Affect Osteoprotegerin and Osteocalcin Levels in Women Differently, Irrespective of Thyroid Function - Shinkov, Alexander D (Libertas Academica, 2014)
Osteoprotegerin (OPG) and osteocalcin (OC) are essential bone proteins. Recent studies have demonstrated that they are not secreted solely by bone cells; they play roles in the vascular function and energy metabolism, and they are influenced by multiple factors. The aim of the current study was to investigate the influence of menopause and age on OPG and OC in women with different thyroid-stimulating hormone (TSH) levels. MATERIAL AND METHODS: We studied 49 women with elevated TSH, 26 with suppressed TSH, and 67 age-matched euthyroid controls. Of them 64 were menstruating and 78 postmenopausal. Body weight, height, waist circumference (WC), body mass index (BMI), serum TSH, free thyroxin (FT4), OPG, and OC were measured. RESULTS: Generally, both OPG and OC were higher in the postmenopausal women than in the menstruating subjects (OPG 3.85 ± 1.49 pmol/L vs. 5.84 ± 2.42 pmol/L, P < 0.001; OC 8.84 ± 3.70 ng/dL vs. 12.87 ± 6.45 ng/dL, P < 0.001), and within the two thyroid dysfunction subgroups and the controls (all P < 0.05). OPG correlated with age (postmenopausal rho = 0.57, P < 0.001; premenopausal rho = 0.31, P = 0.015). Among the premenopausal subjects, OPG was higher in those with low TSH than in the controls (P = 0.048). OC correlated negatively with BMI and WC in the postmenopausal group (Spearman rho = −0.25, P = 0.03 and rho = −0.42, P < 0.001 respectively). OC was higher in the postmenopausal subjects with low TSH than in those with elevated TSH (P = 0.024), and correlated positively with FT4 (rho = 0.40, P = 0.002) and negatively with TSH (rho = −0.29, P = 0.013). CONCLUSIONS: In women, OPG and OC depended differently on age and menopause and, to a lesser extent, on the thyroid function and body composition.